Classed Pathways to Marriage: Hometown Ties, College Networks, and Life after Graduation. Issue 4 (11th January 2021) - Armstrong, Elizabeth A.; Hamilton, Laura T.
Abstract: Objective: This article identifies mechanisms through which social class background shapes the marital outcomes of college‐going white American women. Background: Scholars are interested in the relative influences of ascriptive and achieved characteristics on mate selection. Research indicates that social class background continues to influence the marriage patterns of college‐educated Americans but does not identify the mechanisms through which this occurs. Method: The study analyzes six waves of longitudinal interviews with 45 women from differing social class backgrounds. The first interview was conducted at age 18, when women started college at a Midwestern public university. The final interview was collected at age 30 and was supplemented by a survey collecting the income, education, occupation, and debt of women and their spouses. Results: Women from privileged backgrounds were more likely to marry and married men who earned substantially more than the partners of less privileged women. Differences resulted from lifelong variation in social networks, originating in childhood. College did not interrupt long‐standing exclusionary class networks. After graduation, social class background shaped where women moved, as well as with whom they worked and socialized. Conclusion: Higher education in the contemporary United States may reinforce rather than interrupt class homogamy in marriage, even when students attend the same schools. The role of higher education in shaping classed social networks is in need of further study.